Decreased magnesium level and membrane potential of glaucoma patients - Nnodim, Johnkennedy; Elemba JE, Obioma; Constance, Nwadike; Ukamaka, Edward; Treasure, Njoku-Obi; Folorunso, Jimoh Raifu; Magnus, Nsonwu (Universa Medicina, 2016)
BackgroundOne of the most important sight-threatening eye disorders in ophthalmology is glaucoma. Together with age related macular degeneration it is the most common cause of irreversible blindness. Magnesium (Mg) is considered to improve the ocular blood flow in glaucoma patients and could protect the retinal ganglion cell against oxidative stress. Membrane potential refers to the difference in electrical potential between the intracellular and the extracellular of a biological cell. The objective of this study was to determine the Mg serum level and membrane potential in glucoma subjects.MethodsA case-control study was conducted in eighty confirmed glaucoma patients and eighty normal subjects between 50 to75 years were selected. The serum sodium, potassium and calcium were estimated using Randox Kit. While membrane potential was determined by calculation using Nerst Equation. Magnesium levels were determined by atomic absorption spectrophotometer technique. An independent t-test was used to analyze the data. ResultsThe results obtained showed that the level of Magnesium serum (1.11 ± 0.14 mg/dL) and membrane potential (176.40 ± 42.00 J) was significantly decreased in glaucoma as compared to the controls (2.4 ± 0.68 mg/dL) and (251.76 ± 191.99) (p<0.05). The serum sodium, potassium and calcium were also significantly decreased among glaucoma subjects compared to control (p<0.005).ConclusionThe result probably suggests, that decrease in magnesium aggravates glaucoma while decrease in membrane potential could cause poor energy transmission and hence affect ocular blood flow. Hence, decreased magnesium and membrane potential levels contributes greatly to glaucoma.